A Radical Reworlding: Discourses of Abolition and Neoliberal Resilience in the Covid-19 Pandemic - Tayah Clarke (Studies in Social Justice)
This paper explores the limitations of neoliberal concepts of resilience and the possibilities of abolition in the discourses surrounding the Covid-19 pandemic in Canada. I locate Canada’s state discussions at the outset of the pandemic in 2020 in the neoliberal model of resilience that is rooted in ideologies of individualism and carcerality, rather than the deconstruction of the interdependent systems that create them – despite the temporary questioning of the status quo in political discourse. To contrast the mobilization of neoliberal resilience, I introduce the Doctors for Defunding the Police collective and analyze how they mobilize a more radical praxis by approaching pandemic discourse through a framework of abolition and healing justice. Finally, I draw on Ndlovu-Gatsheni’s (2023) analysis of the components of reworlding from the Global South, locating the praxis of Doctors for Defunding the Police in this tradition due to its rejection of neoliberal individualism, its embrace of alternative subjectivities, and its turn towards a politics of collective care. Ultimately, I argue that while the 2020 resilience discourse afforded an approach to the pandemic that did not fully abandon the population, it remained fundamentally tied to neoliberalism and racial capitalism, whereas the abolitionist response offered a more transformative praxis of reworlding through its commitment to deconstructing harmful systems and reviving a decolonial praxis of collectivity. To conclude, I examine how the contemporary politics of Covid-19 continue to embrace colonial and carceral realities, necessitating a continued abolitionist praxis of reworlding.